ANOTASI PUTUSAN ULTRA PETITA DALAM LINGKUP PERADILAN ADMINISTRASI DI INDONESIA - Martitah Martitah (Faculty of Law, Universitas Diponegoro, 2014)
The existence of administrative tribunals in Indonesia is one of the rechtsstaat pillars. The decision of the Administrative Court is expected to be the main instrument of dispute fulfillment and justice message. Therefore, in accordance with the principle of dominus litis, judges are required to maximize its role in the fulfillment of disputes, including to make dictum of ultra petita, so may reflect society's sense of law justice.Ultra petita decision in the Administrative Court have diverse characters, ultra petita of reformatio in peius, reformatio in melius, repeating the command process, the cancellation decision is not the object of dispute, but is materially related to the object of dispute, the addition of a substantial amar and amar that is declarative.